BASF stabiliser enables high-clarity PP for vaccination syringes. Issue 8 (August 2021) - Unknown
Abstract : Korean company LOTTE Chemical has produced the polypropylene (PP) required for syringes used in Covid-19 vaccinations using BASF's Irgastab®, a non-discolouring processing stabiliser which improves high clarity of medical PP.